Vitamin K supplementation increases vitamin K tissue levels but fails to counteract ectopic calcification in a mouse model for pseudoxanthoma elasticum - Gorgels, Theodorus Gerardus Maria Franciscus; Waarsing, Jan H.; Herfs, Marjolein; Versteeg, Daniëlle; Schönsiegel, Frank; Sato, Toshiro; Schlingemann, Reinier O.; Ivandic, Boris; Vermeer, Cees; Schurgers, Leon J.; Bergen, Arthur A. B. (Journal of molecular medicine, 2011)
Pseudoxanthoma elasticum (PXE) is an autosomal recessive disorder in which calcification of connective tissue leads to pathology in skin, eye and blood vessels. PXE is caused by mutations in ABCC6. High expression of this transporter in the basolateral hepatocyte membrane suggests that it secretes an as-yet elusive factor into the circulation which prevents ectopic calcification. Utilizing our Abcc6−/− mouse model for PXE, we tested the hypothesis that this factor is vitamin K (precursor) (Borst et al. 2008, Cell Cycle). For 3 months, Abcc6−/− and wild-type mice were put on diets containing either the minimum dose of vitamin K required for normal blood coagulation or a dose that was 100 times higher. Vitamin K was supplied as menaquinone-7 (MK-7). Ectopic calcification was monitored in vivo by monthly micro-CT scans of the snout, as the PXE mouse model develops a characteristic connective tissue mineralization at the base of the whiskers. In addition, calcification of kidney arteries was measured by histology. Results show that supplemental MK-7 had no effect on ectopic calcification in Abcc6−/−mice. MK-7 supplementation increased vitamin K levels (in skin, heart and brain) in wild-type and in Abcc6−/− mice. Vitamin K tissue levels did not depend on Abcc6 genotype. In conclusion, dietary MK-7 supplementation increased vitamin K tissue levels in the PXE mouse model but failed to counteract ectopic calcification. Hence, we obtained no support for the hypothesis that Abcc6 transports vitamin K and that PXE can be cured by increasing tissue levels of vitamin K.